Pengaruh Self-Efficacy Dan Motivasi Belajar Terhadap Prestasi Belajar Siswa - Cahya Rohmatul Kharisma; Muhammad Indra Adi Gunawan (Jurnal Pendidikan Agama Islam Miazhar, 2024)
Education is a conscious effort made to prepare students through a series of learning and training activities. Awareness of working together to improve education is the key to success in all fields to create a generation that is healthy, virtuous, capable, skilled and enthusiastic in facing the future without depending on other people. This research aims: 1) to determine the self-efficacy of MA Al-Azhar Menganti Gesik students, 2) to determine the learning motivation of MA Al-Azhar Menganti Gresik students, 3) to determine the learning achievement of MA Al-Azhar Menganti Gresik students, 4) to determine the influence of self-efficacy and learning motivation on the learning achievement of MA Al-Azhar Menganti Gresik students. This research is quantitative research. The population in this study was 199 students. The sampling technique used a simple random sampling technique, namely 50 students as research samples. The data collection method used was a questionnaire. The data analysis technique used is the multiple linear regression equation. Based on this description, there is no significant influence between self-efficacy and learning motivation on the learning achievement of MA Al-Azhar Menganti Gresik students. These results are based on the results of statistical calculation analysis using the multiple linear regression formula, showing the R Square value is 0.020. This means that the influence of self-efficacy and learning motivation on the learning achievement of MA Al-Azhar Menganti Gresik students is 2%. So this research can be considered not to have a significant influence because the magnitude of the influence is too small